2003
DOI: 10.1152/japplphysiol.00185.2003
|View full text |Cite
|
Sign up to set email alerts
|

ATP concentrations and muscle tension increase linearly with muscle contraction

Abstract: Previous studies have suggested that activation of ATP-sensitive P2X receptors in skeletal muscle play a role in mediating the exercise pressor reflex (Li J and Sinoway LI. Am J Physiol Heart Circ Physiol 283: H2636-H2643, 2002). To determine the role ATP plays in this reflex, it is necessary to examine whether muscle interstitial ATP (ATPi) concentrations rise with muscle contraction. Accordingly, in this study, muscle contraction was evoked by electrical stimulation of the L7 and S1 ventral roots of the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 54 publications
3
113
1
2
Order By: Relevance
“…This result might suggest that the above substances are unlikely to be responsible for the sensitization to mechanical stimulus in the ECC group because the heat sensitivities were not altered in the present experiment. In addi-tion, elevation of ATP (Li et al 2003) and BK (Blais et al 1999) concentrations after exercise reaches a peak within a half day; therefore the possibility would seem to be low that these substances are sensitizers involved in DOMS. There might be another or yet unknown substance(s) that sensitize(s) nociceptors specifically to mechanical stimulus.…”
Section: Effects Of Eccmentioning
confidence: 99%
See 2 more Smart Citations
“…This result might suggest that the above substances are unlikely to be responsible for the sensitization to mechanical stimulus in the ECC group because the heat sensitivities were not altered in the present experiment. In addi-tion, elevation of ATP (Li et al 2003) and BK (Blais et al 1999) concentrations after exercise reaches a peak within a half day; therefore the possibility would seem to be low that these substances are sensitizers involved in DOMS. There might be another or yet unknown substance(s) that sensitize(s) nociceptors specifically to mechanical stimulus.…”
Section: Effects Of Eccmentioning
confidence: 99%
“…Eccentric exercise has been widely used in human and animal studies of DOMS, many of which have found histological Friden and Lieber 1998;McCurry and Faulkner 1985), ultrastructural (Newham et al 1983;Ogilvie et al 1988), biochemical Blais et al 1999;Ostrowski et al 1998), and physical (see Proske and Morgan 2001 for review) changes. Lactic acid was long considered to be responsible for DOMS, but this belief has been largely rejected because of the failure of higher levels of lactate to induce soreness in concentric exercise (Armstrong 1984;Schwane et al 1983) or in McArdle's disease (Kazemi-Esfarjani et al 2002), a different time course for soreness and the blood lactate increase after exercise , and other findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many substances are released from exercising muscle: lactate (Tegeder et al, 2002); bradykinin (including kallidin-like pep-tide) (Blais et al, 1999;Boix et al, 2002); ATP (Li et al, 2003); and other substances (Tegeder et al, 2002). Among these substances, bradykinin, glutamate, and ATP are able to induce not only excitation/sensitization of nociceptors, but also changes in expression of neuropeptides and channels in several types of cell (Ferreira et al, 1993;Baker, 2005;Inoue et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ATP rises in skeletal muscle interstitium with contraction 73) , and stimulates P2X receptors on thin fiber muscle afferents 10) , thereby not only stimulating chemically sensitive afferents, but also sensitizing mechanically sensitive afferents 74) . Li and colleagues 70) found that Ī±,Ī²-methylene ATP infused intra-arterially into hindlimb circulation of the decerebrate rats enhanced the pressor response to passive stretch to a larger degree in rats with HF than in healthy controls.…”
Section: Contribution Of Rat Studies To Understanding Mechanisms Undementioning
confidence: 99%